2019
DOI: 10.1515/opag-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Crop growth and viability of seeds on Mars and Moon soil simulants

Abstract: If humans are going to establish a base on the Moon or on Mars they will have to grow their own crops. An option is to use Lunar and Martian regolith. These regoliths are not available for plant growth experiments, therefore NASA has developed regolith simulants. The major goal of this project was to cultivate and harvest crops on these Mars and Moon simulants. The simulants were mixed with organic matter to mimic the addition of residues from earlier harvests. Ten different crops, garden cress, rocket, tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
0
33
1
Order By: Relevance
“…An additional option for increasing regolith N and its N storage capacity would be to till nitrogen containing plants, like clover, into regolith as green fertilizer [ 41 , 42 ], along with the addition of decomposer microorganisms to produce more bioavailable nitrogen via mineralization [ 6 , 43 ]. One study reported that the addition of organic matter in regolith, using grass clippings from Lolium perenne L., resulted in an improvement in plant growth displayed in plant phenology as plants grown in previous studies did not show seed or fruit production [ 44 ]. As fungi and bacteria are routinely placed in cold storage for archiving and research purposes, this process could be replicated for transport to Mars.…”
Section: Discussionmentioning
confidence: 99%
“…An additional option for increasing regolith N and its N storage capacity would be to till nitrogen containing plants, like clover, into regolith as green fertilizer [ 41 , 42 ], along with the addition of decomposer microorganisms to produce more bioavailable nitrogen via mineralization [ 6 , 43 ]. One study reported that the addition of organic matter in regolith, using grass clippings from Lolium perenne L., resulted in an improvement in plant growth displayed in plant phenology as plants grown in previous studies did not show seed or fruit production [ 44 ]. As fungi and bacteria are routinely placed in cold storage for archiving and research purposes, this process could be replicated for transport to Mars.…”
Section: Discussionmentioning
confidence: 99%
“…This work takes place in body of studies that address the capacity of regolith simulants to support plant growth, in the context of ISRU for off-world colonization (Guinan 2018; Eichler et al 2021; Wamelink et al 2019; Wamelink et al 2014). As a precursor to human visitations and future off-world agricultural systems, research regarding plant response to simulated Martian environment is of chief importance.…”
Section: Discussionmentioning
confidence: 99%
“…More globally, this work further confirms the need of soil supplementation outlined by several studies to support the growth of plants. This notably comprises supplementation with nitrogen (through direct NH 4 /NO 3 supplementation or nitrogen fixing bacteria), an essential nutrient for plant growth, which is absent in JSC-Mars-1A simulant (Wamelink et al 2019), although Curiosity Mars Science Laboratory detected nitrate in sedimentary and aeolian deposits within Gale crater (Stern et al 2015). Other reports highlight the importance of soil acidification to improve the plant viability, and the necessity of detoxifying substrates from perchlorates (Eichler et al 2021), through e.g., perchlorate-reducing bacteria (Coates John et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Both species were used in earlier experiments on growing crops on Mars (and Moon) regolith simulants JSC 1A and MMS (Wamelink et al, 2014(Wamelink et al, , 2019. Both plant species germinate quickly (normally within 24 h) have no seed dormancy, rapid growth and grew well on Mars regolith simulant JSC 1A (enriched with organic material) if nutrient solution was supplied (Wamelink et al, 2019). Seeds of both species were sown in pots located in six rectangular trays of 52 by 32 cm (Figure 1A).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Once a week instead of water a standard nutrient solution was supplied (with EC 1.45 mS, pH 5.7). The solution was made by adding 25.2 L Zwakal, 44.2 L BFK, 14.4 L Baskal, 13.8 L Amnitra, 10.4 L Magnitra and 64 L Calsal to 100,000 L of water (standard nutrient solution at WUR, see also Wamelink et al, 2019). Plants were watered daily with paper cups to keep the soil/simulant moist, excessive water was stored in a second tray underneath the tray with the pots.…”
Section: Growth Conditionsmentioning
confidence: 99%